2011
DOI: 10.1021/jp111346s
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Water Dangling OH Bonds in Hydrophobic Hydration Shells. Comparison of Simulation and Experiment

Abstract: Molecular dynamics and electric field strength simulations are performed in order to quantify the structural, dynamic, and vibrational properties of non-H-bonded (dangling) OH groups in the hydration shell of neopentane, as well as in bulk water. The results are found to be in good agreement with the experimentally observed high-frequency (∼3660 cm(-1)) OH band arising from the hydration shell of neopentanol dissolved in HOD/D(2)O, obtained by analyzing variable concentration Raman spectra using multivariate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 46 publications
5
57
0
Order By: Relevance
“…These Raman spectra were further de-convoluted into five Gaussian sub-bands based using established literature methods - see Supplementary Methods (SM). Although the exact band assignments are slightly different in the literature27282930, the consistent idea is that the bands on the low and high frequency sides are related to strong and weak hydrogen-bonded OH features, respectively. In this work, the three components on the low frequency side are assigned to hydrogen-bonded water, while the remaining two high frequency side components are assigned to non-hydrogen-bonded water.…”
Section: Resultsmentioning
confidence: 82%
“…These Raman spectra were further de-convoluted into five Gaussian sub-bands based using established literature methods - see Supplementary Methods (SM). Although the exact band assignments are slightly different in the literature27282930, the consistent idea is that the bands on the low and high frequency sides are related to strong and weak hydrogen-bonded OH features, respectively. In this work, the three components on the low frequency side are assigned to hydrogen-bonded water, while the remaining two high frequency side components are assigned to non-hydrogen-bonded water.…”
Section: Resultsmentioning
confidence: 82%
“…142, 224308 (2015) the presence of such defects in aqueous solutions containing nonpolar solute has been detected in experiments. [165][166][167][168] The authors suggested that translational and rotational retardation of water around a hydrophobe is a consequence of dangling bonds formation, which have slower dynamics.…”
Section: E Dangling-oh Bonds and Hydrogen Bonds Pattern Near A Solutmentioning
confidence: 99%
“…The vibrational spectra of water in hydration shell are different from the spectra in bulk water; however, they overlap seriously with each other and can hardly be distinguished. Recently, plenty of methods were employed to extract the spectra of hydration shell from the overlapping spectra, such as multivariate curve resolution (MCR) method, [26,[34][35][36][37][38] factor analysis (FA), [39][40][41][42][43][44] and fitting analysis. [45] Such as the FA method, it is assumed that the hydration structures are same in some concentration region.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the hydration shell of organic compounds and ions [9,46] were different in different concentration of solutes. MCR method [26,[34][35][36][37][38] assumed that hydration structures kept consistent in sufficiently low concentration region. For example, the hydration shell was thought to be unchanged below 1 M concentration of alkali halide aqueous solutions, [26] and below 1-5 wt % concentration of some organic solutions.…”
Section: Introductionmentioning
confidence: 99%